Association between serum total cholesterol and migraine (Central Medical College Journal, 2022)
Background: There is increasing evidence that migraine with aura is associated with increased risk of ischemic stroke and other vascular disease events. Furthermore migraine has been associated with increased prevalence of specific cardiovascular risk factors, such as hypercholesterolemia has been proposed.Aims and objectives: The present study is aimed at to evaluate the association between serum total cholesterol and migraine.Material and methods: This observational cross sectional study was carried out in Neurology Department in Mymensingh Medical College from December 2016 to November 2018 for a period of 2 years. Patients were selected by purposive sampling. Among 100 patients, 50 grouped as migraineur and 50 grouped as non-migraineur for the study.Results: Serum total cholesterol was significantly higher in migraine than non-migraine. Serum total cholesterol was significantly higher in late age of migraine group and migraine with aura.Conclusion: Elevated level of serum total cholesterol was associated with migraine than non-migraine. Serum total cholesterol was significantly higher in late age of migraine group and migraine with aura.Central Medical College Journal Vol 5 No 1 Jan 2021 PP 41-46